Use of ICT in Mathematics Classroom: Situation, Purpose, and Challenges - Pandeya, Yam Prasad (Siddhajyoti Interdisciplinary Journal, 2023)
The use of Information, and Communication, Technology (ICT) has been a unavoidable tool in the teaching/learning (T/L) process. This article explores the latest situation of practicing ICT in mathematics classrooms along with the challenges being faced in the T/L process. A descriptive survey design under the quantitative method was adopted in this study. The population of the study was all mathematics teachers of Sindhuli district and the teachers who were connected through social media were considered as a sample. Google online survey form was used as the tool for data collection.Collected data were analyzed using a table, percentage, weighted mean, ANOVA, and t-test. The result of this study showed most teachers are using ICT to up-to-date knowledge, enhance teaching skills to obtain teaching resources and additional instructional materials. Similarly, it is found that teachers are using ICT to set out question papers for different tests, assignments, and examinations. Lack of ICT materials and inadequate knowledge and skills for an operating system in the lack of training opportunities were found to be the foremost challenges tothe use of ICT in mathematics teaching.